Piezoelectric co-axial filaments produced by co-extrusion of poly(vinylidene fluoride) and electrically conductive inner and outer layers - Martins, R. S. (2014)
Article first published online: 3 APR 2014 : http://onlinelibrary.wiley.com/doi/10.1002/app.40710/abstract. DOI 10.1002/app.40710.